On-line coupling of supercritical fluid extraction with enantioselective supercritical fluid chromatography-triple quadrupole mass spectrometry for the determination of chiral pesticides in hemp seeds: A proof-of-principle study. (30th March 2022) - Zoccali, Mariosimone; Russo, Marina; Testa Camillo, Maria Rita; Salafia, Fabio; Tranchida, Peter Q.; Dugo, Paola; Mondello, Luigi
Highlights: The first on-line method for the extraction and determination of chiral pesticides. The proposed method fulfills the EU MRL values. Nine hemp seed samples were investigate to their content in chiral pesticides. Abstract: The present research can be considered as a proof-of-principle study focused on the determination of chiral pesticides using a supercritical fluid extraction instrument coupled on-line with an enantioselective supercritical fluid chromatography-triple quadrupole mass spectrometry. To the best of Authors' knowledge, this is the first description of an on-line approach for the extraction and determination of chiral pesticides. Metalaxyl, benalaxyl and dimethenamid were investigated in nine hemp seed samples belonging to four varieties of Cannabis sativa ; only in one case a pesticide was found at levels above the method limit of quantification (LoQ), though within the EU maximum residue level value. The figures-of-merit determined were linearity, precision, limit of detection (LoD), and LoQ. Regression coefficients were between 0.9856 and 0.9973, the LoDs were in the 0.04–0.41 μg kg −1 range, the LoQs were in the 0.12–1.38 μg kg −1 range, while coefficients of variation were between 1 and 3% (10 μg kg −1 level).